Comparing living and working conditions: Germany outperforms the United States - Jan Priewe (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
This paper compares living and working conditions in the U.S. and Germany for the year 2022 with a focus on economic, social and environmental standards. Twelve dimensions of comparison are used, split into 15 themes, which are examined with 80 indicators. Subjective indicators based on polls or surveys, such as happiness or quality of life in general, are explicitly avoided. A special emphasis is placed on median values instead of mean values if data allow. Emphasis is also placed on income and wealth inequality. The methodology, which focuses on only two countries in a granular approach, provides much more detailed information than methodologies used in other studies. This paper is, to the knowledge of the author, the only comprehensive comparison of living conditions in the U.S. and Germany. The result of the comparison shows that Germany scores 23 and the U.S. only 6. The framing of the comparison is the analysis of two different types of capitalism. It underlines the limited role of GDP per capita for the living conditions of the majority of the population while highlighting the impact of institutions and the type of the welfare state.
Keywords: P10; P16; P50; P51; 330; living conditions; quality of life; international comparisons; inequality; National Accounting